RESEARCHING SIMPLICITY AND SOPHISTICATION IN STUDENT WRITING - Breeze, Ruth (International Journal of English Studies, 2008)
The programs WordSmith and VocabProfile were used to research lexical differences between essays written in English by Spanish undergraduates and a set of essays independently judged as being of TWE grade 6 standard. The results indicated that writing by this group of students was generally characterised by low lexical variation, a preponderance of high-frequency words and under-use of academic vocabulary in comparison with the target style. Reasons for the apparent lexical simplicity of this sample of student writing are discussed.